"O dominio do Indios": catequesee e conquista nos sertões do Rio Pomba (1767-1813) - Adriano Toledo Paiva (2009)
This research is an attempt to understand the social and power relationships in the construction of a village in the sertões do Rio Pomba e Peixe dos índios Coropós e Coroados (1767-1813). We studied the processes of creation of the State in the colonial frontier. We problematized the construction of a parish in the Indian domains, assessing the arrangement of this area, as well as conflicts and identities inherent to this process. The main purpose of this research is to retrieve the historicity of the colonized people amid the representations and actions of the ventures of conquest.